(untitled) (Academicia Globe: Inderscience Research, 2025)
The article examines competition as a fundamental element of the functioning of a market economy. Its essence, functions and role in ensuring the efficiency and sustainability of the economic system are revealed. Modern forms of competition and mechanisms of its maintenance, including institutional and regulatory instruments, are analyzed. Special attention is paid to the transformation of the competitive environment in the context of digitalization and the need to adapt antimonopoly policy to new ones technological realities. It is emphasized that competition remains a key factor in economic development and requires constant institutional support.